Determinant Factors That Influence Open Defecation Behavior In Rural Communities In Indonesia - Dzilfiyah Dzilfiyah; Nur Melizza; Anggraini Dwi Kurnia; Nur Lailatul Masruroh (Media Keperawatan Indonesia, 2022)
The problem of sanitation development in Indonesia is a socio-cultural challenge. one of which is the behavior of people who are used to doing OD. OD behavior can be influenced by various factors, both internal and external, including education, occupation, income, knowledge, attitudes, and physical environment. The purpose of this study is to determine the determinant factors that influence the behavior of open defecation. This research uses a cross-sectional approach located in Kedawang Village, Nguling Village, Kedawang Village, Pasuruan Regency. This research was conducted from December 2020 – May 2021. The sampling technique used was purposive sampling with a total sample of 126 people who were selected based on inclusion and exclusion criteria. Data were analyzed using IBM SPSS statistics 20 software with a significance level of 0.05. The majority of respondents, namely 64 people or 50.8% of respondents have attitudes with fewer categories. On average, respondents have less perception of 83 people or 65.9%, lack of knowledge (99.2%), and less physical environment (114%). Meanwhile, the open defecation behavior carried out by the community was in the frequent category (56.3%). The results show that from several factors analyzed, the factors that influence open defecation behavior are attitude (sig 0.000) and perception (sig 0.000). Factors that influence open defecation behavior are attitudes and perceptions. Poor attitudes and perceptions will result in people doing open defecation behavior.